Artificial Feed from Organic Waste for Carp (Cyprinus carpio L.) - Wolly Candramila; Muhammad Taufik Riandi; Dani Abdillah; Eko Widodo (UNIVERSITAS NEGERI PADANG, 2020)
Carp (Cyprinus carpio L.) is one of the widely cultivated fishes in Indonesia. Utilization of organic waste from the traditional market such as chicken intestines, corn husk, and water spinach stems into artificial feed for carp (Cyprinus carpio L.) var. Majalaya is discussed in this study. Compared to the commercial feed commonly used by fish farmers in Pontianak, artificial feed with a protein content of 30% showed the best growth rate of body length and weight, and highest feed efficiency. With the proper cultivating condition, artificial feed presents a huge opportunity to be an alternative solution to reduce the cost of carp farm production.